2009
DOI: 10.1002/pmic.200800545
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylation as means of reducing sample complexity to enable quantitative proteomics

Abstract: Quantitative proteomics is a rapidly expanding field, in particular, the application to clinical biomarker studies for diagnosis or prognosis of diseases, and the systematic analysis of protein functions in biological systems. Isolation of a class of peptides or a subproteome enables reduction of sample complexity, which is essential to perform sensitive, quantitative analyses over a wider dynamic range of protein concentrations. Glycosylation is one of the most frequent PTMs, and glycans have unique chemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…However, it has been shown that in silico calculation indicates that on average 1/20 of the tryptic peptides have the N-X-S/T sequence known as the N-glycosylation consensus sequence (49). Considering the microheterogeneity of glycoforms in the redundant N-glycosylation sites, we believe that the glycoform-focused reverse glycoblotting technique greatly contributes to reducing the complexity of biological samples and accelerates discovery research of potential biomarkers on the basis of multiplex MRM MS (50,51).…”
Section: Application Of Reverse Glycoblotting-assisted Multiplex Mrm mentioning
confidence: 99%
“…However, it has been shown that in silico calculation indicates that on average 1/20 of the tryptic peptides have the N-X-S/T sequence known as the N-glycosylation consensus sequence (49). Considering the microheterogeneity of glycoforms in the redundant N-glycosylation sites, we believe that the glycoform-focused reverse glycoblotting technique greatly contributes to reducing the complexity of biological samples and accelerates discovery research of potential biomarkers on the basis of multiplex MRM MS (50,51).…”
Section: Application Of Reverse Glycoblotting-assisted Multiplex Mrm mentioning
confidence: 99%
“…There is, therefore, general agreement that to detect glycoproteins, some with potential as disease biomarkers, effective sample fractionation or enrichment strategies are required. This can be achieved by first subdividing the proteome into smaller, less complex fractions, or selective enrichment of the glycoproteome subset by leveraging the unique properties of their glycans [], followed by separate analysis of individual fractions to achieve a more in‐depth coverage of the sample proteome. The suitability of the chosen technology or combination of technologies depends primarily on the biological questions to be answered and the need to enhance coverage of the targeted glycoproteome to ensure maximum interpretation and downstream utility of the data.…”
Section: Enrichment Strategies For Lower Abundant Glycoproteinsmentioning
confidence: 99%
“…Another strategy, which has been applied in combination with SRM for the quantification of low abundance proteins in plasma, focuses on the N -glycosite subproteome [31,32]. This approach is based on the fact that most proteins present at the cell surface or secreted from tissue are glycosylated and are therefore likely to be detected in plasma.…”
Section: Selected Reaction Monitoring Mass Spectrometry For Plasma Bimentioning
confidence: 99%